2019
DOI: 10.1371/journal.pone.0211559
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 renal risk variants promote cholesterol accumulation in tissues and cultured macrophages from APOL1 transgenic mice

Abstract: Apolipoprotein L1 ( APOL1 ) genetic variants G1 and G2, compared to the common allele G0, are major risk factors for non-diabetic kidney disease in African descent populations. APOL1 is a minor protein component of HDL, as well as being expressed in podocytes and vascular cells. Reverse cholesterol transport involves the transport of cholesterol to HDL by cellular ATP-binding cassette; ABCA1 and ABCG1 with subsequent delivery from peripheral tissues to the liver. With impaired reverse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 24 publications
5
48
0
Order By: Relevance
“…None of the BAC-APOL1 mice spontaneously developed proteinuria ( Fig. 1D), which is consistent with the original description of these mouse models (13,14). When proteinuria was induced by interbreeding with a model of HIV-associated nephropathy ( Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…None of the BAC-APOL1 mice spontaneously developed proteinuria ( Fig. 1D), which is consistent with the original description of these mouse models (13,14). When proteinuria was induced by interbreeding with a model of HIV-associated nephropathy ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…Three transgenic mouse lines expressing a human bacterial artificial chromosome (BAC) encompassing the entire APOL1 genomic region for either the G0, G1, or G2 alleles have been described (13,14). These mice express APOL1 under native gene regulatory regions and appear to replicate the gene expression pattern observed in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a study using the population from the Women's Health Initiative, no association was found between the high-risk genotype and cardiovascular event precursors, including left ventricular hypertrophy [137]. Ryu et al [141] showed that APOL1-G1 and -G2 genetic variants were associated with higher intracellular cholesterol content, ABCA1 and ABCG1 suppression, and, in consequence, with reduced reverse cholesterol transport. The results of their study suggest that impaired cholesterol efflux capacity observed in APOL1 renal risk variant macrophages may stimulate, in vivo, the formation of foam cells.…”
Section: Cardiovascular Risk Related To Modifications Of Hdl Particlementioning
confidence: 99%
“…However, the involved mechanism of the generation of foam cells in FSGS is far from clear. In a recent report, Ryu et al (85) showed that expression of APOL1 RRVs diminishes cholesterol efflux in macrophages, resulting in the alteration of their phenotype. These investigators harvested monocytes from the kidney, spleen, and bone marrow from wild-type, APOL1 G0, APOL1 G1, and APOL1 G2 transgenic mice.…”
Section: Cross-talk Of Apol1 With Lipidsmentioning
confidence: 99%